Enhanced Chlorella vulgaris Buitenzorg growth by Photon Flux Density Alteration in Serial Bubble Column Photobioreactors - Wijanarko, Anondho; Sendjaya, Dianursanti Antonius Yudi; Gozan, Misri; Soemantojo, Roekmijati Widaningroem; Witarto, Arief Budi; Asami, Kazuhiro; Ohtaguchi, Kazuhisa (ASEAN Journal of Chemical Engineering, 2007)
Micro algae are photolitotrophs that perform oxygenic photosynthesis and capable of accumulating a large amount of CO2, using an inducible CO2 concentrating mechanism (CCM). These characteristics make the micro algae potentially useful for removal and utilization of CO2 emitted from industrial plant. Generally, the usage of photosynthetic microorganism in CO2 fixation and biomass production for the economically viable commodities have been increased and significantly improved as a solution for this problem. Using these facts and previous research results using Anabaena cylindrica IAM M1 and Spirulina platensis IAM M 135, enhancement of CO2 fixation and biomass production by Chlorella vulgaris Buitenzorg with photon flux density alteration along with an increasing of culture biomass during the cellular growth period, was implemented in this research. The photon flux density used in this alteration was the maximum light for Chlorella’s maximum growth rate ( I mmax,opt ). The cultivation of Chlorella vulgaris Buitenzorg in the Benneck basal medium operating conditions: T, 29oC; P, 1.0 atm; UG, 2.4m/h; CO2, 10%; using Philip Halogen Lamp 20W/12V/50Hz as the light source and three bubble column photobioreactors arranged in series order with each having a volume of 0.200dm3. Results had shown that the photon flux density alteration as a whole could increase around 60% the biomass production of Chlorella vulgaris and around 7% the CO2 fixation ability, compared to constant photon flux density outcomes. This experiment also showed that the noncompetitive inhibition of [HCO3-] as carbon source substrate is affected significantly during the cultivation in both of alteration and continuous photon flux density.